2014
DOI: 10.1117/12.2058642
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of radiation dose and strain based on an erbium-doped fiber ring laser incorporating a fiber Bragg grating

Abstract: We propose a sensing scheme of an erbium-doped fiber (EDF) ring laser for multi-monitoring of radiation dose and strain simultaneously. The EDF and fiber Bragg grating (FBG) are exploited as sensing probes for simultaneous measurement of radiation dose and strain. The output power and the lasing wavelength of the proposed EDF laser are changed by increasing the radiation dose and strain, respectively. The radiation and strain sensitivities were measured to be 8.4 dB/km•Gy and 0.81 pm/με, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the same year of 2014, FBG-based sensors based on FRL did not just show its charm in the area of AE sensing. Shim et al [ 68 ] also found its potential in strain and radiation dose sensing. Knowing that the EDF has high sensitivity to radiation, they did not just use the EDF-based fiber laser as a tool to enhance the SNR or narrow the 3-dB bandwidth of the sensor, but ingeniously using the EDF as a sensing probe for radiation dose detection.…”
Section: Sensing Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year of 2014, FBG-based sensors based on FRL did not just show its charm in the area of AE sensing. Shim et al [ 68 ] also found its potential in strain and radiation dose sensing. Knowing that the EDF has high sensitivity to radiation, they did not just use the EDF-based fiber laser as a tool to enhance the SNR or narrow the 3-dB bandwidth of the sensor, but ingeniously using the EDF as a sensing probe for radiation dose detection.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…Qualities of different measurement parameters have been summarized in this article among different structure of sensing head. For example, the highest sensitivities of temperature sensing of MZI-based sensors, FPI-based sensors and Sagnac-based sensors are −1.747 nm/°C [ 28 ], 0.249 nm/°C [ 56 ], 1.739 nm/°C [ 62 ], respectively; the highest sensitivities of strain sensing among MZI-based sensors, and FBG-based sensors are 0.148 nm/με [ 38 ], 0.81 pm/με [ 68 ]. From the temperature sensitivity among different sensors, it can be seen that the MZI-based sensor and the Sagnac-based sensor can be designed to gain an extremely high sensitivity.…”
Section: Sensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, in [45], employing Twincore fiber in line with a FBG as a WSF, the authors manufactured a laser with an SMSR of 40 dB in an operation range of 0-980 µϵ for obtained a sensitivity of 1.48 pm µϵ −1 . According to [46] and [47], an FBG generates a laser emission with a sensitivity of 0.81 pm µϵ −1 (0-2000 µϵ) and 1.11 pm µϵ −1 (0-1200 µϵ). As reported by [48], polarization mode beat frequency (PMBF) is used to beating two polarization modes, reaching a laser emission of 28.58 dB of SMSR, in the strain range of 0-1150 µϵ and obtained a maximum sensitivity of 0.2498 pm µϵ −1 .…”
Section: Introductionmentioning
confidence: 99%